Makna Bantuan dan Proses Pembelajaran Informal: Resiliensi Keluarga Penerima Program Keluarga Harapan (PKH) - Ahmad Fauzi; Nining Purwaningsih; M. Syadeli Hanafi (ARZUSIN, 2025)
Although the Program Keluarga Harapan (PKH) is designed to enhance the welfare and self-reliance of vulnerable families through financial assistance combined with educational activities such as P2K2/P3K, its implementation effectiveness does not always align with the policy design. This study aims to explore the experiences of PKH beneficiaries in the subdistricts of Cadasari and Karangtanjung and the City of Cilegon to understand how the assistance is interpreted, implemented, and perceived in relation to behavioral change and the development of beneficiaries’ capacity for self-reliance. Adopting a qualitative approach with an interpretative phenomenological method, the study draws on in-depth interviews, program observations, and document analysis. The findings reveal four main themes: assistance is more often perceived as a routine entitlement than as a transformative instrument; low financial and digital literacy constrains the optimal utilization of benefits; P2K2/P3K activities tend to function as administrative procedures rather than genuine learning spaces; and local resilience develops through informal coping strategies grounded in social capital. These findings indicate that PKH beneficiaries are not in a passive position but actively develop adaptive strategies, although these strategies are not yet fully oriented toward long-term economic self-reliance. The study concludes that PKH effectiveness requires a shift in implementation from mere benefit distribution to an empowerment-oriented model that strengthens financial and digital capacities, enhances the quality of adult-learning-based mentoring, and integrates local social capital into the program’s formal mechanisms. This study contributes to the development of an adaptive social protection approach in Indonesia and offers implementable recommendations for strengthening literacy and mentoring that are sensitive to local contexts.